Intravital Multiphoton Examination of Implant-Associated Staphylococcus aureus Biofilm Infection - Gries, Casey M.; Rivas, Zuivanna; Chen, Justin; Lo, David D. (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial infections associated with implanted medical devices represents a healthcare crisis due to their persistence, antibiotic tolerance, and immune avoidance. Indwelling devices are rapidly coated with host plasma and extracellular matrix proteins which can then be exploited by bacterial pathogens for adherence and subsequent biofilm development. Our understanding of the host-pathogen interface that determines the fate of biofilm-mediated infections is limited to the experimental models employed by laboratories studying these organisms. Current in vivo models of biofilm-mediated infection, while certainly useful, are typically limited to end-point analyses of bacterial burden enumeration, immune cell profiling, and cytokine/chemokine analysis. Thus, with these models, the complex, real-time assessment of biofilm development and innate immune cell activity remains imperceptible. Here, we describe a novel murine biofilm infection model employing time-lapse intravital multiphoton microscopy which permits concurrent and real-time visualization of Staphylococcus aureus biofilm formation and immune cell activity. Using cell tracking, we found that S. aureus biofilms impede neutrophil chemotaxis, redirecting their migration patterns to prevent biofilm invasion. This approach is the first to directly examine device-associated biofilm development and host-pathogen interactions and will serve to both further our understanding of infection development and help reveal the effects of future antibiofilm treatment strategies.